Memória, imaginário e subjetividade: notas a uma categoria estética à rememoração da história de horror brasileira - Cardoso, Fernando da Silva; Gomes, Graciele Maria Coelho de Andrade; Carvalho, Mário de Faria (Diálogos Latinoamericanos, 2019)
This study discusses the theoretical-analytical concept “aesthetic memory”. We argue for the relevance of this concept for the field of memory studies as a possible tool for the reconstruction of human rights violations. We analyze sensitive elements of remembrance of violence that occurred during the Brazilian civil-military dictatorship present in works by the plastic artist from Pernambuco Abelardo da Hora. Abelardo da Hora’s artistic production uses image regimes, symbols, archetypes and schèmes that, based on mystical and imagistic elements, invoke the horror and the state of exception of the military dictatorship in Brazil. We conclude that concept aesthetic memory can contribute to the analysis of the subjectivity of subject-victims in the construction of collective memories about the recent past of serious violations of human rights.